2018
DOI: 10.1055/s-0038-1673367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Attitudes, and Factors Motivating Conscientious Objection toward Reproductive Health among Medical Students

Abstract: Objective We have evaluated the prevalence of and the motivating factors behind the refusal to provide reproductive health services and the ethical knowledge of the subject among medical students from the Escola Bahiana de Medicina e Saúde Pública, in the state of Bahia, Brazil. Methods The present cross-sectional study involved 120 medical students. A questionnaire was utilized. The dependent variables were students' objections (or not) regarding three clinical reproductive health cases: abortion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
2
16
0
2
Order By: Relevance
“…Faúndes et al 27 explored opinions regarding the criminalization of abortion and found low approval (9.9%) for imprisoning women who have had abortions, especially among older, non-religious students. Being religious was the factor most closely associated with restrictive positions 27,29,31 .…”
Section: Article (Year Of Publication)mentioning
confidence: 96%
See 4 more Smart Citations
“…Faúndes et al 27 explored opinions regarding the criminalization of abortion and found low approval (9.9%) for imprisoning women who have had abortions, especially among older, non-religious students. Being religious was the factor most closely associated with restrictive positions 27,29,31 .…”
Section: Article (Year Of Publication)mentioning
confidence: 96%
“…A single article described the results of a census of legal abortion services in the country, analyzing their structure and operations, the characteristics of the women who received care at these services and the perspective of their professionals 14 ; another five studies, of local scope, described the characteristics of women admitted to hospitals for abortion following a rape, the reasons for the decision to have an abortion and repercussions for personal and day-to-day relationships 17,18,19,20,21 . Most studies investigated the behavior, knowledge and opinion of agents involved in providing legal abortion care, whether they were health professionals 16,22,23,24 or medical students 25,26,27,28,29,30,31 . Three studies addressed the theme of malformations and court authorizations for abortion 15,32,33 (Table 2).…”
Section: General Article Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations